Shared Physical Custody Interdisciplinary Insights in Child Custody Arrangements - Bernardi, Laura; Mortelmans, Dimitri (European Studies of Population, 2021)
This open access book provides an overview of the ever-growing phenomenon of children in shared physical custody thereby providing legal, psychological, family sociological and demographical insights. It describes how, despite the long evolution of broken families, only the last decade has seen a radical shift in custody arrangements for children in divorced families and the gender revolution in parenting which is taking place. The chapters have a national or cross-national perspective and address topics like prevalence and types of shared physical custody, legal frames regulating custody arrangements, stability and changes in arrangements across the life course of children, socio‐economic, psychological, social well-being of various family members involved in different custody arrangements. With the book being an interdisciplinary collaboration, it is interesting read for social scientists in demography, sociology, psychology, law and policy makers with an interest family studies and custody arrangements.